Class I Polyhydroxyalkanoate (PHA) Synthase Increased Polylactic Acid Production in Engineered Escherichia Coli - Shi, Mengxun; Li, Mengdi; Yang, Anran; Miao, Xue; Yang, Liu; Pandhal, Jagroop; Zou, Huibin (Frontiers in Bioengineering and Biotechnology, 2022)
Polylactic acid (PLA), homopolymer of lactic acid (LA), is a bio-derived, biocompatible and biodegradable polyester. The evolved class II PHA synthase (PhaC1Ps6-19) was commonly utilized in the de novo biosynthesis of PLA from biomass. This study tested alternative class I PHA synthase (PhaCCs) from Chromobacterium sp. USM2 in engineered Escherichia coli for the de novo biosynthesis of PLA from glucose. The results indicated that PhaCCs had better performance in PLA production than that of class II synthase PhaC1Ps6-19. In addition, SulA gene was engineered in PLA producing strains for morphological engineering. The morphologically engineered strains present increased PLA production. This study also tested fused propionyl-CoA transferase and lactate dehydrogenase A (fused PctCp/LdhA) in engineered E. coli and found that fused PctCp/LdhA did not apparently improve the PLA production. After systematic engineering, highest PLA production was achieved by E. coli MS6 (with PhaCCs and sulA), which can produce up to 955.0 mg/L of PLA in fed-batch fermentation with the cell dry weights of 2.23%, the average molecular weight of produced PLA can reach 21,000.